Quality of life and income level of Kelantan state poverty in Malaysia - Iskandar Hasan Tan Abdullah; Nur Azuki Yusuff; Rosdi Abd Rahman (2016)
Recent studies of poverty have showed the advantage of breaking down a population into subgroups or district along